2020
DOI: 10.15414/afz.2020.23.03.147-154
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Cercospora beticola to fungicides in Slovakia

Abstract: The fungus Cercospora beticola Sacc. is the one of the most important pathogens on the sugar beet. The frequent application of fungicides with the same mode of action increase a risk of development of resistant strains of the pathogen. Occurrence of C. beticola resistant strains has been never researched in Slovakia. In this work, C. beticola isolates were collected from 10 localities of Slovakia and analysed for fungicide resistance in laboratory conditions. Nine fungicides with different mode of action were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…8 (Plan Tonic + Plan Tonic). It corresponds with our previous findings (Hudec et al 2020) where picoxystrobin (included in the preparation Acanto) reached a low inhibition effect on the mycelial growth of C. beticola in laboratory conditions. Bolton et al (2012) compared the laboratory and field efficacy of tetraconazole.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…8 (Plan Tonic + Plan Tonic). It corresponds with our previous findings (Hudec et al 2020) where picoxystrobin (included in the preparation Acanto) reached a low inhibition effect on the mycelial growth of C. beticola in laboratory conditions. Bolton et al (2012) compared the laboratory and field efficacy of tetraconazole.…”
Section: Resultssupporting
confidence: 92%
“…DMI fungicides are broadly used in the fungicide treatment of sugar beet against CLS. While FRAC considers the DMi fungicides (e.g., tetraconazole) as a middle-risk group of resistance development, other authors found an increase in less susceptible strains of C. beticola in the field (Hudec et al 2020). Cercospora beticola isolates originated from treated plots are usually less sensitive to the fungicides than those that originated from untreated plots.…”
Section: Resultsmentioning
confidence: 99%
“…Based on its constituent compounds, propiconazole belongs to the triazole fungicide, which inhibits fungal growth by inhibiting sterol biosynthesis, an essential component in fungal cell defense (Rouabhi 2010). Propiconazole can inhibit the growth of C. beticola (Hudec et al 2020) and A. helianthi (Usha et al 2019). Evaluated for mycelial growth and conidial germination can determine the sensitivity of pathogenic fungi to fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also emphasized that field isolates of C. beticola with EC 50 value >1.0 μg/mL for pyraclostrobin needed to be monitored closely (Secor et al, 2010). Currently, QoI-resistant strains of C. beticola were found in the United States (Bolton et al, 2013), Canada (Trueman et al, 2013), Slovakia (Hudec et al, 2020), Japan (Kayamori et al, 2020) and Serbia (Balandžić et al, 2020). Previous reports also demonstrated that resistance to QoI was attributed to a point mutation in Cyt-b gene, including the amino acid substitution of alanine for glycine at codon 143 (G143A), the substitution of phenylalanine with leucine at codon 129 (F129L) or substitution of glycine with arginine at codon 143 (G143R) (Bolton et al, 2013;Ma et al, 2018;Dixon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%